PENGARUH GAYA KEPEMIMPINAN DAN KOMPETENSI TERHADAP MOTIVASI DAN PRESTASI KERJA DI TRANS RITEL INDONESIA MEDAN - SUNARYO . (LP2MTBM MAKARIOZ, 2020)
Competition in the retail sector is currently getting tighter, this is shown by the number of retail businesses now popping up inIndonesia, especially in Medan. It takes a certain value for the company to be able to survive in this retail business, one ofwhich is that the company must have good value compared to other companies in managing its human resources. It isundeniable that good human resource management will be able to encourage the company to quickly achieve its goals. We,human resources owned by the company, have the perception that their lives are guaranteed by the company, so they willwork totality and are motivated to improve their work performance. Job performance does not only happen to workers in allbusiness spheres, including retail companies. The results of this study indicate that leadership style has a positive andsignificant effect on work motivation. Furthermore, competence has a positive and significant effect on employee motivation.Furthermore, this study also shows that leadership style, competence and work motivation directly and significantly influencejob performance.